Synthesis of hierarchically porous mixed metal oxide structures - Koo, Ricmond Yu Xiang (Nanyang Technological University, 2022)
Multimodal porous structured materials have attracted considerable attention due to their large surface area, high porosity, and pore accessibility. Multi-component metal oxides (MMOs) that have multiscale porous architectures are of particular appeal for various applications such as catalysis and batteries. Here we report a one-pot synthesis approach to form ternary MMOs structures with an ordered hierarchical porous structure with bimodal pore sizes. This new approach may open up new pathways toward synthesis of other multimodal porous MMOs and advanced materials combinations.